A survey on performance management of operating rooms and a new KPI proposal. (10th August 2020) - Sonmez, Volkan; Pintelon, Liliane
Abstract: Performance management of operating rooms is of great importance in hospital management. From the patients' point of view, operating room capacity management ensures available capacity when needed and thus ensuring short (er) waiting time. From the hospital point of view, efficiently and effectively managing these expensive resources is a major concern. Because there are too many performance indicators with a lack of standardization on definitions and there is no one‐size‐fit‐all metric that can assess the overall performance, how to measure is still a challenging question. This paper starts with describing the operating room's characteristics and presents a systematic literature survey exploring different sources for information on operating room performance management. The literature is screened for lists of performance indicators currently used by managers. Aside from the nature of indicators, the way these indicators are used is also investigated. The literature ends with the suggestion of a new key performance indicator (overall operating room effectiveness [OORE]) that is intended to be used in measuring the overall performance of operating rooms from a lean thinking perspective. To increase the ability of finding root causes of low performance, a delay categorization framework is also proposed. Implementation of the KPI is illustrated using a real‐world data. In the conclusion, all the elements studied are brought together, and recommendations for research and practice are formulated.